Incidence and risk factors for incomplete HBV DNA suppression in HIV/HBV‐co‐infected patients initiating tenofovir‐based therapy. Issue 4 (30th July 2013) - Hafkin, J. S.; Osborn, M. K.; Localio, A. R.; Amorosa, V. K.; Kostman, J. R.; Stern, J. J.; De La, P.; Mounzer, K.; Frank, I.; Gross, R.; Chang, K.‐M.; Lo Re, V.
Summary Suppression of hepatitis B virus (HBV)‐DNA to undetectable levels is an important goal for HIV/HBV‐co‐infected patients receiving anti‐HBV‐active antiretroviral therapy (ART), and current guidelines recommend that this outcome should be reached by 1 year of treatment. However, the proportion of patients that fail to achieve an undetectable HBV DNA at this time point and its determinants remain unknown in clinical practice. The objective of this study was to determine the incidence and risk factors for incomplete HBV suppression following 1 year of tenofovir‐based ART. We performed a cohort study among tenofovir‐treated HIV/HBV‐co‐infected patients. Patients had HBV viraemia, initiated tenofovir‐based ART and had HBV DNA measured at 1 year of therapy. The primary outcome was incomplete HBV suppression (HBV DNA ≥2.6 log IU/mL) at 1 year. Logistic regression determined odds ratio (ORs) of incomplete HBV suppression for risk factors of interest. Among 133 patients, 54% (95% CI, 46–63%) had incomplete HBV suppression at 1 year. Incomplete suppression was associated with higher baseline HBV DNA (OR, 1.46 per log IU/mL increase; 95% CI, 1.1–1.94) and detectable HIV viraemia at 1 year (OR, 2.52; 95% CI, 1.19–5.32). Among 66 patients with suppressed HIV RNA at 1 year, 28 (42%) failed to achieve an undetectable HBV DNA. Failure to suppress HBV DNA by 1 year occurred in a sizeable proportion of tenofovir‐treated HIV/HBV‐co‐infected patients. Higher HBV DNA and detectable HIV viraemia were risk factors for incomplete HBV suppression.